Alaska visitors’ knowledge about invasive species in a warming arctic and sub-arctic - Michele Remer; Izabella R. Block; Elizabeth E. Perry; Jennifer I. Schmidt; Jianguo Liu (Biological Invasions, 2026)
As the climate warms and sea ice continues to melt, an increase in overall shipping traffic to the Arctic and to local communities is expected. Specifically, an increase in cruise ship traffic has led to higher numbers of visitors to the Arctic and sub-Arctic. As a secondary effect of increased human activity in this region, invasive species prevention and removal will become a priority, especially as species’ ranges continue to shift with the warming climate. Thus, it is important to have a baseline of visitor knowledge about invasive species in the region to promote robust monitoring. To evaluate visitor knowledge, we conducted visitor intercept surveys in three Alaskan communities that experience tourism. Results show that owning watercraft is associated with an increase in knowledge, but increased knowledge did not lead to any changes in behavior. In addition, increased invasive species knowledge did not differ between visitor groups. Our research demonstrates the need to consider the potential spread of invasive species due to tourism and a need to focus on both systemic policy changes and educational campaigns to encourage cleaning gear brought on travels.

Play and peril: Displacement drivers and types across recreation motivations in crowding and wildfire-prone southern California national forests - Alyssa S. Thomas; Erin E. Budzyn; Elizabeth E. Perry; Brian A. Peterson; José J. Sánchez (Journal of Outdoor Recreation and Tourism, 2025)

Exposure to residential greenness, perceived stress, and depressive symptoms in a North American preconception cohort - Cameron J. Reimer; Mary D. Willis; Amelia K. Wesselink; Perry Hystad; Erin J. Campbell; Elizabeth E. Hatch; Kipruto Kirwa; Jaimie L. Gradus; Marco Vinceti; Lauren A. Wise; Marcia Pescador Jimenez (Environmental Research, 2024)

Scoping the lines: Assessing the mountain biking research terrain and calling for a holistic scholarship agenda - Katelyn P. Kuklinski; Kimberly J. Coleman; Jessica E. Leahy; Elizabeth E. Perry; Emily Reinhardt; Luke Briccetti (Journal of Outdoor Recreation and Tourism, 2024)

Ambient air pollution and rate of spontaneous abortion - Amelia K. Wesselink; Kipruto Kirwa; Perry Hystad; Joel D. Kaufman; Adam A. Szpiro; Mary D. Willis; David A. Savitz; Jonathan I. Levy; Kenneth J. Rothman; Ellen M. Mikkelsen; Anne Sofie Dam Laursen; Elizabeth E. Hatch; et al. (Environmental Research, 2024)

Reprint of: COVID-19 messaging in U.S. state parks: Extensions of the outdoor recreation strategies and practices framework unmasked by the pandemic - Elizabeth E. Perry; Kimberly J. Coleman; Tatiana A. Iretskaia; Jordan M. Baer; Liesl F. Magnus; Peter R. Pettengill (Journal of Outdoor Recreation and Tourism, 2023)

Park Visitors’ Place Attachment and Climate Change-related Displacement: Potential Shifts in Who, Where, and When - Elizabeth E. Perry; Xiao Xiao; John M. Nettles; Tatiana A. Iretskaia; Robert E. Manning (Environmental Management, 2021)